To solve this system using substitution, we can substitute the expression for x from the second equation into the first equation and then solve for y.
Substitute x = 5y - 1 into the first equation:
2(5y - 1) + 6y = -18
10y - 2 + 6y = -18
16y - 2 = -18
16y = -16
y = -1
Now that we have found the value of y, we can substitute it back into the second equation to find x:
x = 5(-1) - 1
x = -5 - 1
x = -6
Therefore, the solution to the system of equations is x = -6 and y = -1.
Solve the system of two equations using substitution.
2x+6y=−18
x=5y−1
1 answer